Being the Facilitator: A Brief Research Report on the Motivation of the Choreographer and Dance Maker to Work With Heterogeneous Groups in a Community Dance Setting - Bilitza, Mia Sophia (Frontiers in Psychology, 2021)
In inclusive dance settings, where people with different abilities and talents come together, the role of facilitators is essential in guiding the process of inclusion. Their behaviour gives sensitive information to the individual about one´s status within the own-group affiliation (Cremer, 2002, p. 1336). Even today, very little research on the motivation for facilitating inclusivity in dance contexts exists. This case study will examine the facilitator´s motivation by juxtaposing current theory next to experiences of seven experts of contemporary dance facilitation in Europe. Good opportunities for meaningful interactions can be created in a dance setting: it promotes a deeper sense of community, gives us the feeling of belonging, generates respect and inclusion, and helps to prevent the feeling of loneliness ( Elin & Boswell, 2004; Kaufmann, 2006; Whatley, 2007). This research report sheds light on the motivation of being the facilitator of dance for heterogeneous groups and reveals three factors from the data. First, to be led by an artistic motivation, second, to have a vision in terms of changing the society, and third, to have another private or personal motivation. The motivation of the facilitator is regarded as highly important for inclusive work, as the person who facilitates plays a key role in these successful processes of inclusion (Miesera et al., 2019).